2003
DOI: 10.1093/jaoac/86.4.775
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Foods: New Enrichment Procedure for TECRA Salmonella Visual Immunoassay Using a Single RV(R10) Only, TT Only, or Dual RV(R10) and TT Selective Enrichment Broths (AOAC Official Method 998.09): Collaborative Study

Abstract: A collaborative study was conducted to compare a new enrichment procedure for the TECRA® Salmonella Visual Immunoassay (TSVIA) with the reference method given in the U.S. Food and Drug Administration's Bacteriological Analytical Manual (7th Ed.). Three food types (milk powder, pepper, and soy flour) were analyzed in Australia and 3 food types (milk chocolate, dried egg, and raw turkey) were analyzed in the United States. Thirty-eight collaborators participated in the study. The TECRA method was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although this study tested a limited number of retail meat and poultry samples, it was apparent that RV medium was the superior selective enrichment broth for BAM compared with TT. An earlier study (Hughes et al, 2003 ) did a pairwise comparison of RVR10 and TT for the TECRA Salmonella Visual Immunoassay and did not find a significant difference ( p > 0.05). A recent study (Broadway et al, 2021 ) reported a 1.4% Salmonella prevalence rate (out of 865 retail samples) using the USDA protocol (USDA, 2021), much more effective compared with BAM.…”
Section: Discussionmentioning
confidence: 90%
“…Although this study tested a limited number of retail meat and poultry samples, it was apparent that RV medium was the superior selective enrichment broth for BAM compared with TT. An earlier study (Hughes et al, 2003 ) did a pairwise comparison of RVR10 and TT for the TECRA Salmonella Visual Immunoassay and did not find a significant difference ( p > 0.05). A recent study (Broadway et al, 2021 ) reported a 1.4% Salmonella prevalence rate (out of 865 retail samples) using the USDA protocol (USDA, 2021), much more effective compared with BAM.…”
Section: Discussionmentioning
confidence: 90%
“…The next goal was to shorten the screening workflow. As the M broth is considered a post‐enrichment step (Hughes et al ), the real‐time assay was evaluated at the selective enrichment step: the Rappaport‐Vassiliadis R10 (RVR) broth. The results of testing 191 meat samples in RVR broth using the real‐time PCR assay showed 100% concordance when compared to the results of the 3M TECRA kit for the same set of food samples (Table ), similar results were obtained using veterinary samples (Goodman et al ).…”
Section: Resultsmentioning
confidence: 99%
“…However, an enrichment step is still required to detect small numbers of Salmonella in food samples. This step may consist of non-selective enrichment with buffered peptone water (BPW) and selective enrichment with Rappaport-Vassiliadis (RV) or tetrathionate [ 6 ]. These enrichment broths have been directly utilized for Salmonella DNA template preparation.…”
Section: Introductionmentioning
confidence: 99%